Cyclic Compression Response and Strain Rate Sensitivity of Graphene Oxide‐Reinforced Epoxy Nanocomposites - Colak, Ozgen; Bakbak, Okan (Wiley, 2026)
ABSTRACT Compressive loading–unloading and oligo cyclic tests were performed on neat epoxy and GO‐epoxy nanocomposites containing 0.1 and 0.5 wt% graphene oxide (GO) to investigate the effects of GO content and strain rate on modulus evolution and damage development. The tests targeted the elastic, yield, and viscoplastic regimes while minimizing low‐cycle fatigue. The strain rate sensitivity factor and damage parameter, which are defined considering the initial elasticity modulus and modulus during unloading, were calculated for neat epoxy and GO‐epoxy nanocomposites. Rate‐dependent compression experiments indicate that the GO‐epoxy nanocomposite with 0.1 wt% GO exhibits approximately 2.5 times higher strain rate sensitivity in this range compared to the nanocomposite containing 0.5 wt% GO. The results indicate that in neat epoxy, the modulus decreases at the second cycle but recovers in later cycles due to cyclic hardening and polymer chain alignment. In contrast, GO‐reinforced nanocomposites consistently show higher unloading modulus than neat epoxy. During oligo cyclic loading, neat epoxy and GO‐epoxy nanocomposites exhibit linear loading and nonlinear unloading behavior. Stress–strain responses are nearly identical between monotonic and oligo cyclic tests, except for slightly higher stress in the final cycle of cyclic loading, indicating minimal influence of short‐term loading history on mechanical behavior.